KONSEP DIRI, KECERDASAN EMOSIONAL, TINGKAT STRES, DAN STRATEGI KOPING REMAJA PADA BERBAGAI MODEL PEMBELAJARAN - Prihatina, Restu Dwi; Latifah, Melly; Johan, Irni Rahmayani (Jurnal Ilmu Keluarga dan Konsumen, 2012)
This study aimed to analyze the characteristics of adolescent, family characteristics, self-concept, emotional intelligence, stress levels, and coping strategies in various learning models of the highschool level. In addition, the study aimed to analyze the relationship between self-concept and emotional intelligence with stress level and coping strategies of adolescent. The study was conducted at one of senior high school in the Bogor City. Adolescent involved in the study were students in grade XI of science class from learning model of acceleration, international school, and reguler which amounted 86 students and selected purposively. Data were collected through self-reporting techniques. Data were analyzed by descriptive, different test, and correlation test. This study found that adolescent emotional intelligence different significantly based learning model. Emotional intelligence associated significantly with adolescent self-concept. Self-concept and emotional intelligence of the adolescent also associated significantly with the level of stress and coping strategies.